Maximizing Performance Through Reviewing Leadership Style And Organizational Citizenship Behavior At Bank Sahabat Sampoerna Kolaka Branch - Fadillah Dwi Noviastuty; Almansyah Rundu Wonua; Hanif Kurniadi (Student Scientific Creativity Journal, 2023)
The advancement or decline of an organization is fundamentally intertwined with the accomplishments of its workforce. Hence, each company consistently endeavors to enhance employee performance, either through the implementation of specific leadership techniques or the observation of organizational citizenship behavior displayed by its workforce. Therefore, this study seeks to delve deeper into the influence and interplay between variables related to leadership style and Organizational Citizenship Behavior in relation to employee performance at Bank Sahabat Sampoerna's Kolaka Branch. This research encompasses all employees at Bank Sahabat Sampoerna's Kolaka Branch, encompassing the entire population and adopting a saturated sampling methodology. Data analysis was conducted using the Structural Equation Modeling (SEM-PLS) approach. The results of this investigation confirm the impact that the utilized leadership style and employee organizational citizenship behavior have on employee performance.